9. Q2a
Save videos to My Cheatsheet for later, for easy studying.
Video Solution
Q1
Q2
Q3
L1
L2
L3
Similar Question 1
<p>Expand and simplify.</p><p><code class='latex inline'>-0.4h(3h-2)-0.3h(2h+3)</code></p>
Similar Question 2
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 4(x+2)-2 x </code></p>
Similar Question 3
<p>Expand and simplify.</p><p><code class='latex inline'>3(a-5)-2(a+4)</code></p>
Similar Questions
Learning Path
L1 Quick Intro to Factoring Trinomial with Leading a
L2 Introduction to Factoring ax^2+bx+c
L3 Factoring ax^2+bx+c, ex1
Now You Try
<p>Expand and simplify.</p><p><code class='latex inline'>-0.4h(3h-2)-0.3h(2h+3)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>3k(k+5)+4k(k-3)</code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 3(x+2 y)-2(x+3 y) </code></p>
<p>Expand and Simplify.</p><p><code class='latex inline'> \displaystyle 3(y + 4) + 6(y - 2) </code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 8(t+4)-(t-9) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>2a[3a(a+4)]-a(2a-3)]</code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 2 y-(5-y) </code></p>
<p> Expand and simplify as much as possible. </p><p><code class='latex inline'> \displaystyle (a - ab^2) - a(-a + b^2) </code></p>
<p>Simplify. <code class='latex inline'>\displaystyle 3 x+2(1-x) </code></p>
<p>Order the numbers from least to greatest.</p><p><code class='latex inline'>\displaystyle -2(4+b)+4(b-5) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>3a(2a+3)+4(a^2+2a-4)</code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 2(z-1)+3(z-2) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>\dfrac{2}{3}(3m+5)+\dfrac{2}{5}(5m-4)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>4[3-2(b+1)]+3[4-2(b+1)]</code></p>
<p>Expand and Simplify.</p><p><code class='latex inline'> \displaystyle -4(6b - 3) - (3b + 5) </code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle -3(a-1)-2 a </code></p>
<p><code class='latex inline'>\displaystyle\begin{array}{c}\end{array}</code></p><p><code class='latex inline'>\displaystyle 5(x-6)-3(x-7) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>\dfrac{1}{5}(-5a+2b)-\dfrac{3}{4}(4a-b)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>-4(4d-3)-2(3d+4)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>3(a-5)-2(a+4)</code></p>
<p>Simplify by combining like terms.</p><p><code class='latex inline'>\displaystyle x(3-y)+y(x+6) </code></p>
<p><code class='latex inline'>\displaystyle\begin{array}{c}\end{array}</code></p><p><code class='latex inline'>\displaystyle (2 x+3 y)+(4 x-3 y) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>-2[4-(y-4)]-3[2+(y-3)]</code></p>
<p>Evaluate each expression for x-value of <code class='latex inline'>-2, -1, 0, 3</code>, and <code class='latex inline'>10</code>. Describe any difficulties that occur.</p><p><code class='latex inline'>\displaystyle (x - 6)(x - 2) -(x - 11)(x + 2)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>\dfrac{1}{2}(6a-5c)-\dfrac{1}{3}(6a+4c)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>\dfrac{1}{4}(8x+3)+\dfrac{1}{3}(6x+2)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>4(r-3)-3(r+2)+2(r-5)</code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 3m(6m^2-5m + 4) -(4m^3 - 8m^2 + 9) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>5g(2g-3)-3(2g^2-4g+3)</code></p>
<p>Simplify the expression <code class='latex inline'>\displaystyle 5 d(7-3)-16 d+3 \cdot 2 d </code>.</p><p> <code class='latex inline'>\displaystyle \begin{array}{ll}\text { A } 10 d & \text { C } 21 d \ \text { B } 14 d & \text { D } 25 d\end{array} </code></p>
<p> Use the distributive law to expand the following. Simplify your answers by collecting the like terms.</p><p><code class='latex inline'>5(4x^2 - 9y^2 + 5z^2) - 3(2x^2 - 8y^2 + 6 z^2)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>5(x+4)+3(x-6)</code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 5 m-2 n+5(n-m) </code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>3(a+2)+5(a-3)-2(a+4)</code></p>
<p>Expand and simplify.</p><p><code class='latex inline'>0.3(c+2)+0.5(2c-5)</code></p>
<p>Order the numbers from least to greatest.</p><p><code class='latex inline'>\displaystyle (k-m)-(m-k) </code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 2(x+3)+4(x+2) </code></p>
<p>Which expression best represents a simpler form of <code class='latex inline'>\displaystyle 4 m+3(m+n) ? </code> <code class='latex inline'>\displaystyle \begin{array}{llll}\text { (A) } 7 m+3 n & \text { (B) } 4 m+3 m n & \text { (C) } 3 m+4 n & \text { (D) } 7 m^{2}+3 n\end{array} </code></p>
<p><code class='latex inline'>\displaystyle -(x+y)+3(x-4 y) </code></p><p><code class='latex inline'>\displaystyle -x+y+3 x-4 y </code></p><p><code class='latex inline'>\displaystyle 2 x-3 y </code></p>
<p> Use the distributive law to expand the following. Simplify your answers by collecting the like terms.</p><p><code class='latex inline'>-3(9x^2 + 2xy) - 6(-4xy + 4) + 7(6 + x^2)</code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 2 x+y-z-(x-y-z) </code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle 4(x+2)-2 x </code></p>
<p>Simplify.</p><p><code class='latex inline'>\displaystyle (3 c-4 d)-(5 c-4 d) </code></p>
How did you do?
I failed
I think I failed
I think I got it
I got it
Another question?
Found an error or missing video? We'll update it within the hour! 👉
Report it
Save videos to My Cheatsheet for later, for easy studying.